2007
DOI: 10.1021/jp071131q
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Methyl Formate with TiC(100):  Comparison of Experiment with Density Functional Calculations

Abstract: Titanium carbide is an important tribological material used as an antiwear coating on mechanical components. The TiC(100) surface has demonstrated interesting low-temperature chemistry with a variety of adsorbates, including methyl formate, the simplest ester and a model for this chemical functionality found in many aerospace lubricants. In an effort to identify and characterize surface adsorption and reaction products, we have undertaken a comparison of theoretical results employing density functional methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The results of Kim et al for the dissociation of methyl formate over TiC(100) using HREELS showed that oxygen-terminated methoxyl groups bound preferentially to Ti sites and carbon-terminated methyl groups to carbon sites. 77 These results suggest that the nonmetal surface atoms of ceramics do play a direct role in surface reactions and may present special chemistry not accessible when using TMs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The results of Kim et al for the dissociation of methyl formate over TiC(100) using HREELS showed that oxygen-terminated methoxyl groups bound preferentially to Ti sites and carbon-terminated methyl groups to carbon sites. 77 These results suggest that the nonmetal surface atoms of ceramics do play a direct role in surface reactions and may present special chemistry not accessible when using TMs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…FeAl(1 00)T PD, [146] XPS [146] methanol FeAl(110)T PD, [147] UPS, [147] XPS [147] methanol TiAl(1 00)T PD, [146] XPS [146] methanol TiAl TPD, [147] UPS, [147] XPS [147] methanol Co/Mo(110)T PD, [148] HREELS [148] methanol FeS 2 (1 00)T PD, [149] AES, [149] XPS, [149] HREELS, [149] PAX [149] methyl acetate Ni(111)T PD, [113] RAIRS [113] methyl formate W(1 00)T PRS [150] methyl formate C/W(1 00)T PRS [150] methyl formate TiC( 100)X PS, [151] HREELS, [151,152] TPD, [151] DFT [152] methyl formate VC (1 00)X PS, [151] HREELS, [151] TPD [151] methyl formate Ni(111)T PD, [113] RAIRS [113] phenol Pt(111)T PD, [153] HREELS, [153] XPS [153] propanal WC DFT, [154] TPD, [154] HREELS [154] propanal Mo 2 CD FT, [99] TPD [99] vinyl acetate Pd(111)R AIRS, [155] TPD, [155] DFT [155] 1-propanol Pt(111)D FT [156]…”
Section: Dft Calculationsmentioning
confidence: 99%